2022
DOI: 10.3390/bioengineering9080406
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Long Noncoding RNAs in Hepatocellular Carcinoma: Classification, Molecular Mechanisms, and Significant Therapeutic Potentials

Abstract: Hepatocellular carcinoma (HCC) is the most common and serious type of primary liver cancer. HCC patients have a high death rate and poor prognosis due to the lack of clear signs and inadequate treatment interventions. However, the molecular pathways that underpin HCC pathogenesis remain unclear. Long non-coding RNAs (lncRNAs), a new type of RNAs, have been found to play important roles in HCC. LncRNAs have the ability to influence gene expression and protein activity. Dysregulation of lncRNAs has been linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 337 publications
0
4
0
Order By: Relevance
“…Numerous studies have provided compelling evidence to demonstrate the popular roles of lncRNAs as ceRNAs in cancer development [ 36 ]. In this study, the results indicated that the site-specific m6A modification of PSMA3-AS1 and MIR22HG enhanced the stability of lncRNAs in GCSCs, thus having a promotive role on PSMA3-AS1 and MIR22HG as ceRNAs in tumorigenesis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have provided compelling evidence to demonstrate the popular roles of lncRNAs as ceRNAs in cancer development [ 36 ]. In this study, the results indicated that the site-specific m6A modification of PSMA3-AS1 and MIR22HG enhanced the stability of lncRNAs in GCSCs, thus having a promotive role on PSMA3-AS1 and MIR22HG as ceRNAs in tumorigenesis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA can modulate gene expression at epigenetic, transcriptional, and post transcriptional levels through interacting with DNA, mRNA, protein, and microRNA (miRNA) to be involved in a wide variety of diseases, including solid and hematological tumors [9][10][11]. For HCC, a large number of lncRNAs have been identified to be aberrantly expressed in HCC and contribute to tumor development by affecting various biological processes such as cell proliferation, apoptosis, migration, invasion, angiogenesis and drug resistance, exhibiting their potential as prognostic and diagnostic biomarkers as well as therapeutic targets for HCC [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This transcriptomics data, which includes messenger RNAs (mRNAs) and ncRNAs such as micro RNAs (miRNAs), lncRNAs, and circular RNAs (circRNAs), have been selected for studying HCC detection. 4 Compared with other ncRNAs, lncRNAs were the most of ncRNAs with length exceeding 200 nucleotides and are more tissue- or condition-specific than mRNAs. 5 There are several studies showing that lncRNAs are the regulators related to multiple major biological processes in various types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Moreover, previous studies have revealed that lncRNAs are critical in regulating HCC, functioning either as oncogenes or as tumor suppressor genes. 4 For instance, increased levels of lncRNA CDKN2B-AS1 are associated with an unfavorable prognosis in patients with HCC. 10 CDKN2B-AS1 plays a role in advancing HCC, as it interacts with E2F transcription factor 1 (E2F) in HCC cells to enhance the expression of oncogenes G protein subunit alpha Z (GNAZ).…”
Section: Introductionmentioning
confidence: 99%